DE MILHO (Zea mays L.) À AGROCEL: O PAPEL DO MILHO HÍBRIDO AGROCERES NA MODERNIZAÇÃO DA AGRICULTURA NO BRASIL (1945-1960) - Menoncin, Jaine (2017)
The objective of this dissertation is to analyze the process of implementation of hybrid corn seed in Brazil, focusing on the company Sementes Agroceres S.A. (SASA) and its relationship with US philanthropic agencies in a post WW II context. Specifically, this study will address the influence of agencies associated with entrepreneur Nelson Rockefeller such as the American International Association for Economic and Social Development (AIA) and the International Basic Economy Co. (IBEC) on the process in question. The experiences of Brazilian researchers and proposed a cooperation agreement that resulted in the creation of Sementes Agroceres S/A (SASA). The cut used is from 1945 to 1960, a period that has been selected since the founding of Agroceres by Brazilian agronomists, until its effective implementation in the market, a period that also precedes its productive diversification. The sources used are company commemorative books of 25, 50 and 70 years, institutional reports and correspondence between Brazilian and North American agronomists. In this sense, the aim is to treat hybrid corn, not only as part of the introduction of a new system of political and economic relations with the United States, but also to understand hybrid maize as an element of modernization of Brazilian agriculture, as and "modern" in a country considered underdeveloped. It is a work related to Environmental History, since corn is discussed as an important factor in this development process, and also as a propeller of changes and impacts in the relation of man to the planting this seed.